2020
DOI: 10.1021/acs.chemmater.0c03482
|View full text |Cite
|
Sign up to set email alerts
|

Van der Waals Bound Organic Semiconductor/2D-Material Hybrid Heterosystems: Intrinsic Epitaxial Alignment of Perfluoropentacene Films on Transition Metal Dichalcogenides

Abstract: Hybrid systems consisting of transition metal dichalcogenides (TMDCs) and organic semiconductors (OSCs) are promising candidates for future optoelectronic device architectures, as they combine the outstanding charge transport properties of TMDCs with the high photoabsorption cross-section and the ability to tailor the energy levels of OSCs through synthetic means. Since crystalline organic layers have very anisotropic optical absorption and emission characteristics, their azimuthal alignment is an important pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 54 publications
0
18
0
Order By: Relevance
“…In previous work it was demonstrated that the growth of PFP films on graphene leads to a new π-stacked polymorph (PSP) where all molecules are flat lying and adopt a slip-stacked molecular packing . Later this interface stabilized phase was also found upon PFP growth on hexagonal basal planes of other weakly interacting substrates, like graphite, hexagonal boron nitride (hBN), or transition metal dichalcogenides (TMDCs). ,,, This raises the question of whether such an interface stabilized phase exists also for smaller perfluoro­acenes. Therefore, we have studied the film growth of PFT and PFA on graphene, which were characterized by means of XRD and NEXAFS.…”
Section: Resultsmentioning
confidence: 99%
“…In previous work it was demonstrated that the growth of PFP films on graphene leads to a new π-stacked polymorph (PSP) where all molecules are flat lying and adopt a slip-stacked molecular packing . Later this interface stabilized phase was also found upon PFP growth on hexagonal basal planes of other weakly interacting substrates, like graphite, hexagonal boron nitride (hBN), or transition metal dichalcogenides (TMDCs). ,,, This raises the question of whether such an interface stabilized phase exists also for smaller perfluoro­acenes. Therefore, we have studied the film growth of PFT and PFA on graphene, which were characterized by means of XRD and NEXAFS.…”
Section: Resultsmentioning
confidence: 99%
“…Rearrangements of the molecules frequently occur at the interface so that deviations from the known crystallographic packing of the molecules appear. Successful explanations of organic epitaxy are based on lattice mismatch calculations and ledge-directed or angle-directed crystallization. , A classification of epitaxial types, including both rigid and flexible lattices, was recently published …”
Section: Introductionmentioning
confidence: 99%
“…While it is tempting to assume that all large aromatic systems will lie π-face-on, the difference in orientation between H 2 Pc and CuPc on MoS 2 indicates that additional factors need to be considered. While some work on this topic has been performed, , many questions remain unanswered. One difficulty in studying organic adlayer orientation and morphology is the common presence of surface contaminants.…”
mentioning
confidence: 99%